Gene Expression Regulation by Agonist-Independent Constitutive Signaling of Melanocortin-1 Receptor - Seong, Ikjoo (Korean Endocrine Society, 2014)
BACKGROUND: Melanocortin-1 receptor (Mc1r), a key signaling receptor for melanogenesis, has been reported to mediate migration of B16F10 melanoma cells. Interestingly, this activity appears to be a part of the constitutive signaling of Mc1r. METHODS: We carried out small interfering RNA-mediated knock-down of Mc1r on murine melanoma B16F10 cells and performed microarray analysis to characterize changes in the gene expression profile. RESULTS: We isolated 22 and four genes whose expression decreased and increased, respectively, by 2.5-fold or higher as the result of Mc1r knock-down. Several down-regulated genes have been proposed to be involved in cell migration. Among these genes are several members of the chemokine gene family. CONCLUSION: We provide a gene set for further functional analyses of Mc1r. The Mc1r target genes we present may be particularly relevant for understanding the ligand-independent activity of Mc1r. Further examination of the mode of action may lead to novel strategies in regulating the migration and metastasis of melanoma cells.